Heart failure and “payment in full”: What does the law say? - Klinck, M. E. (SA Heart Journal, 2017)
One of the major practical manifestations of health law and ethics for practitioners in private practice occurs in their interactions with medical schemes. This article sets out the complete legal framework applicable to medical schemes cover as a manifestation of the human right of access to healthcare and the right of access to social security. It is proposed that the legal framework can and should be used as neutral ground so as to ensure that patients obtain funding that provides meaningful cover of the costs of appropriate care.